Towards an Axiological Training Inputs from Physical Education (Review) (Revista científica Olimpia, 2021)
In the pedagogical field, values ​​are acquired in the social dimension of educational practice through interaction, they are discovered and learned; This is based on the fact that, due to the contents, the pedagogical and methodological practices, the interpersonal relationships and the relationships between the school, the family and the community, the internalization of values ​​is promoted in multiple ways. Talking about this subject requires a long and personal dialogue with great sincerity. It must be a sharing of experiences that come from the daily events of what has happened day by day on this path of life. That is why the performance of the Physical Education teacher must be in accordance with the norms and principles established by society. A Physical Education in and for life is proposed towards an axiological formation that allows to question and interpret this field of work. Therefore, it is important to move through reflective thinking towards paths that lead to enhancing the initial training of the student. The purpose of this research is to assume axiological thinking to debate pedagogical actions and thus rethink education as a space for social transformation. The methodology of this study is based on field research. Undoubtedly, this research represents a potential of complexities that has nuances of articulation and connections at the theoretical, ontological, epistemological, and axiological levels.
Keywords: physical education, values, teacher training